Apostrof (Apostrophe) as a Means of Disambiguation in Number According to Antistih (Anti-Verse) Principle - Aleksandr D. Bolshakov (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The author of the article considers the development of the differentiating function of the apostrof (apostrophe), which is realized in the contemporary Church Slavonic language in the pronominal paradigm. The comparison of facts in grammars and old-printed editions shows that the application of apostrophe-dissimilator was not presupposed by the Grammar of 1648, and appeared in the course of the work of the Moscow Print Yard correctors (from the Service Book of 1655). It first appeared in the forms yazhe, izhe with the support of productive forms (ya, i), then it spread to the forms im, imzhe (by external analogy with other forms of DatPl) and further to the rest of the pronominal homoforms (by internal analogy). The development of this spelling innovation was consistently reflected in the Moscow editions of the second half of the 17 th century up to its stage-by-stage codification in grammars of 1721, 1723, 1725 and 1733. The pronominal nature of the apostrophe-dissimilator predetermined the limitations in its functioning; however, the acquisition of a differentiating function became a necessary stage in the formation of the system of antistih (anti-verse) in its modern form. The expansion of apostrophe functioning, which has a precedent in the Grammar by F. Maximov (1723), may contribute to the logical completion of this formation. Also, the obtained data on the development of the apostrof (apostrophe) differentiating function can be used to identify Moscow editions along with other innovations, introduced in the period of the Nikon’s correctors work.